Evidence-based best-bets for nutrition-secure climate-resilient policy pathways in Zambia - Jennings, Stewart (2023)
Our aim is to inform policy pathways that contribute to equitable climate-resilient nutrition security. We want to engage with stakeholders in working towards this goal, focusing on how our evidence can be used to support existing policies and upcoming policy processes, or suggest new polices if necessary.